If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7t + 6 = 8t Reorder the terms: 6 + 7t = 8t Solving 6 + 7t = 8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8t' to each side of the equation. 6 + 7t + -8t = 8t + -8t Combine like terms: 7t + -8t = -1t 6 + -1t = 8t + -8t Combine like terms: 8t + -8t = 0 6 + -1t = 0 Add '-6' to each side of the equation. 6 + -6 + -1t = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1t = 0 + -6 -1t = 0 + -6 Combine like terms: 0 + -6 = -6 -1t = -6 Divide each side by '-1'. t = 6 Simplifying t = 6
| x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= | | -2-9r=10+2r+10 | | 20(16x+8)=12 | | 7-10n+5n=18-96 | | x^4-4x^3+4x^2-36x-45=0 | | 3f=8-5f | | 2.1x-8.9=3.9x-8.9-1.8x | | X-4y=3b | | 3(x-1)=2x-3+3 | | 8w=9+9w | | 6x^2-10x-7=0 | | (x/4)+8=-8 | | X=10x-12 | | Y^2-y+.25=0 | | 5=8m+4-7 | | 37-2x=6+7(-3x-1) | | -5+5m=-10+4m | | -4+q=-13 | | 64x^2-5=30 | | -3p=-2p-9 | | 10(c-2)+5=3+c-18 |